Prognostic factors for change in self-reported anxiety and depression in spondyloarthritis patients: data from the population-based SpAScania cohort from southern Sweden. (4th May 2018) - Meesters, JJL; Bergman, S; Haglund, E; Jacobsson, LTH; Petersson, IF; Bremander, A
Abstract : Objectives : Anxiety and depression symptoms are more common in patients with spondyloarthritis (SpA) than in the general population. This study describes prognostic factors for change in self-reported anxiety and depression over 2 years in a well-defined SpA cohort. Method : In 2009, 3716 adult patients from the SpAScania cohort received a postal questionnaire to assess quality of life (QoL) and physical and mental functioning. A follow-up survey was performed in 2011. The Hospital Anxiety and Depression Scale indicated 'no', 'possible', and 'probable' cases of anxiety and depression. Transitions between the three different categories were analysed and logistic regression analysis determined prognostic factors (patient-reported outcomes and characteristics) for improvement or deterioration. Results : In total, 1629 SpA patients responded to both surveys (44%) (mean ± SD age 55.8 ± 13.1 years, disease duration 14.6 ± 11.7 years); 27% had ankylosing spondylitis, 55% psoriatic arthritis, and 18% undifferentiated SpA. The proportion of patients reporting possible/probable anxiety decreased from 31% to 25% over 2 years, while no changes in depression were seen. Factors associated with deterioration or improvement were largely the same for anxiety as for depression: fatigue, general health, QoL, level of functioning, disease activity, and self-efficacy. However, reporting chronic widespread pain (CWP) at baseline increased the risk of becoming depressed and decreased the probability of recovering from anxiety. Conclusion : Self-reported anxiety and depression is common and fairly stable over time in SpA patients. The association between mental health and CWP indicates that both comorbidities need to be acknowledged and treated in the clinic.